miR-26a inhibits atherosclerosis progression by targeting TRPC3 - Min Feng; Daqian Xu; Lirui Wang (Cell & Bioscience, 2018)
Abstract Background Atherosclerosis, a chronic multi-factorial vascular disease, has become a predominant cause of a variety of cardiovascular disorders. miR-26a was previously reported to be involved in atherosclerosis progression. However, the underlying mechanism of miR-26a in atherosclerosis remains to be further explained. Methods High-fat diet (HFD)-fed apolipoprotein E (apoE)−/− mice and oxidized low-density lipoprotein (ox-LDL)-stimulated human aortic endothelial cells (HAECs) were established as in vivo and in vitro models of atherosclerosis. RT-qPCR and western blot analysis were performed to measure the expression of miR-26a and transient receptor potential canonical 3 (TRPC3), respectively. Binding between miR-26a and TRPC3 was predicted with bioinformatics software and verified using a dual luciferase reporter assay. The effects of miR-26a on the lipid accumulation, atherosclerotic lesion, and inflammatory response in HFD-fed apoE−/− mice were investigated by a colorimetric enzymatic assay system, hematoxylin–eosin and oil-Red-O staining, and ELISA, respectively. Additionally, the effects of miR-26a or combined with TRPC3 on cell viability, apoptosis and the nuclear factor-kappa B (NF-κB) pathway in ox-LDL-stimulated HAECs were evaluated by MTT assay, TUNEL assay, and western blot, respectively. Results miR-26a was downregulated in HFD-fed apoE−/− mice and ox-LDL-stimulated HAECs. miR-26a overexpression inhibited the pathogenesis of atherosclerosis by attenuating hyperlipidemia, atherosclerotic lesion and suppressing inflammatory response in HFD-fed apoE−/− mice. Moreover, miR-26a overexpression suppressed inflammatory response and the NF-κB pathway, promoted cell viability and inhibited apoptosis in ox-LDL-stimulated HAECs. Additionally, TRPC3 was demonstrated to be a direct target of miR-26a. Enforced expression of TRPC3 reversed the effects of miR-26a on cell viability, apoptosis, and the NF-κB pathway in ox-LDL-treated HAECs. Conclusions miR-26a alleviated the development of atherosclerosis by regulating TRPC3, providing a potential target for atherosclerosis treatment.